2019
DOI: 10.14311/cej.2019.03.0030
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on Shear Strength Characteristics of Soil-Rock Mixtures

Abstract: The shear strength of soil-rock mixtures (S-RM) is an important parameter affecting the stability of engineering. Therefore, taking the S-RM along Shiyan-Tianshui Expressway (G7011) in Qinba Mountains as the research object, large-scale direct shear tests on S-RM with different rock content and water content were conducted in this paper. The test results show that the shear deformation curves of S-RM samples are basically the same, which can be divided into four stages: elastic deformation, initial yield, stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In the fractured rock strength prediction model, most of the machine learning algorithms are the theoretical basis, through the search for data experience to establish a prediction model. Zhongping, Y et al established the shear strength prediction model of the soil-rock mixture by using the fitting of solid test data and numerical test data 9 . Yu, L et al established a jointed rock strength prediction model based on acoustic emission characteristic parameters 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In the fractured rock strength prediction model, most of the machine learning algorithms are the theoretical basis, through the search for data experience to establish a prediction model. Zhongping, Y et al established the shear strength prediction model of the soil-rock mixture by using the fitting of solid test data and numerical test data 9 . Yu, L et al established a jointed rock strength prediction model based on acoustic emission characteristic parameters 10 .…”
Section: Introductionmentioning
confidence: 99%
“…e change of water content will affect the shear strength of soil, thus affecting the bonding strength of soilrock interface. Zhao et al [21] studied the shear strength change of soil-rock mixture under different factors through laboratory tests, and it was found that the effect degree of water content on the shear strength of soil-rock mixture is just next to the rock content.…”
Section: Introductionmentioning
confidence: 99%